Quanah Parker Great Chief of the Comanches - Gonzalez, Catherine Troxell; Mitchell, Mark (Eakin Press Austin, Texas, 1987)
Relates, in simple text and illustrations, the life of the last Comanche chief who, among other achievements, helped his people make the change from traditional ways to the new white culture.
Includes bibliographical references
Keywords: Parker, Quanah, -- 1845?-1911; Comanche Indians. -- Indians of North America